2002
DOI: 10.1038/nature01126
|View full text |Cite|
|
Sign up to set email alerts
|

Histone methylation by the Drosophila epigenetic transcriptional regulator Ash1

Abstract: The establishment and maintenance of mitotic and meiotic stable (epigenetic) transcription patterns is fundamental for cell determination and function. Epigenetic regulation of transcription is mediated by epigenetic activators and repressors, and may require the establishment, 'spreading' and maintenance of epigenetic signals. Although these signals remain unclear, it has been proposed that chromatin structure and consequently post-translational modification of histones may have an important role in epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
214
6
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(228 citation statements)
references
References 28 publications
5
214
6
3
Order By: Relevance
“…MLL1 has been found to associate with other epigenetic regulators, such as the HAT CBP (Ernst et al 2001) andINI1 (Rozenblatt-Rosen et al 1998), a subunit of the SWI/SNF nucleosome remodeling complex, and one study found MLL1 to reside in a large protein assembly containing subunits capable of regulating transcription preinitiation, nucleosome remodeling, histone acetylation, and histone methylation (Nakamura et al 2002). A similarly orchestrated epigenetic regulation was demonstrated for the Drosophila Trithorax-like protein Ash1, a histone methyltransferase (HMT) capable of methylating Lys 4 and Lys 9 of histone H3 and Lys 20 on histone H4 (Beisel et al 2002). The Ash1-specific methylation imprint was found to displace HP1 and PcG proteins, which are normally bound to repressed genes, and instead facilitates the binding of the Brahma chromatin remodeling complex (Beisel et al 2002).…”
Section: Setting Trithorax Imprintsmentioning
confidence: 98%
“…MLL1 has been found to associate with other epigenetic regulators, such as the HAT CBP (Ernst et al 2001) andINI1 (Rozenblatt-Rosen et al 1998), a subunit of the SWI/SNF nucleosome remodeling complex, and one study found MLL1 to reside in a large protein assembly containing subunits capable of regulating transcription preinitiation, nucleosome remodeling, histone acetylation, and histone methylation (Nakamura et al 2002). A similarly orchestrated epigenetic regulation was demonstrated for the Drosophila Trithorax-like protein Ash1, a histone methyltransferase (HMT) capable of methylating Lys 4 and Lys 9 of histone H3 and Lys 20 on histone H4 (Beisel et al 2002). The Ash1-specific methylation imprint was found to displace HP1 and PcG proteins, which are normally bound to repressed genes, and instead facilitates the binding of the Brahma chromatin remodeling complex (Beisel et al 2002).…”
Section: Setting Trithorax Imprintsmentioning
confidence: 98%
“…Recent studies by Sanchez-Elsner (Sanchez-Elsner et al 2006) further showed that these intergenic transcripts from the TRE at the Ubx locus mediate transcriptional activation of Ubx by recruiting the epigenetic regulator Ash1 to the TRE elements. Ash1 is a histone methyltransferase (HMT) that promotes transcriptional activation by trimethylating H3K4, H3K9, and H4K20 (Beisel et al 2002) and is essential for the tissue-specific expression of Ubx (Beisel et al 2002 and references therein). Therefore, intergenic transcripts derived from the TRE locus mediate the recruitment of Ash1 to the TRE DNA elements of Ubx.…”
Section: Bithorax Complex (Bx-c) In Drosophilamentioning
confidence: 99%
“…Results using siRNA-knockdown approach indicate that ARID1A is required for cell-cycle arrest (26). Ubiquitination of H2B was associated with transcriptional activation (45). For example, ubiquitinated H2B has been identified in the yeast Saccharomyces cerevisiae, and mutation of the conserved ubiquitination site is shown to confer defects in mitotic cell growth and meiosis.…”
mentioning
confidence: 99%